2018
DOI: 10.1088/2040-8986/aaf2ab
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and incoherent switching of cavity solitons in an optically injected VCSEL

Abstract: Intensity and population dynamics are studied for two different switching techniques used for creation and deletion of cavity solitons (CSs) in vertical cavity surface emitting lasers with external injection. For coherent switching, we use transient Gaussian pulse in and out of phase with the external injection respectively for switching on and off. Studies of the regimes of 10% and 20% above laser threshold revealed that Hopf instability is the cause of more switching energy required for creation of CSs in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Here we set Γ (D)=0.560D+0.293, Δ=−α+2δ/Γ and δ (D)=0.155D−0.146, where Γ(D) is associated with the gain linewidth, while δ(D) is the detuning between the reference frequency and the frequency where the gain is maximum. We only briefly recall that for the parameter values of d=0.052, α=4, b=10 −4 , σ=4×10 −2 , θ=−2, β=0.125, the system shows bistability and instabilities required for the formation of spatial structures and CSs [13].…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we set Γ (D)=0.560D+0.293, Δ=−α+2δ/Γ and δ (D)=0.155D−0.146, where Γ(D) is associated with the gain linewidth, while δ(D) is the detuning between the reference frequency and the frequency where the gain is maximum. We only briefly recall that for the parameter values of d=0.052, α=4, b=10 −4 , σ=4×10 −2 , θ=−2, β=0.125, the system shows bistability and instabilities required for the formation of spatial structures and CSs [13].…”
Section: The Modelmentioning
confidence: 99%
“…A major advancement in the area of optical communication and processing has been the introduction of cavity solitons (CSs) as independent and addressable information bits [11,12]. These localized spots of light sitting on a lowintensity background radiation exist in a variety of nonlinear optical cavities with different characteristics and potential applications owing to their capability of being switched ON/ OFF individually [13][14][15][16][17] or in two/multiple-peak states [18][19][20], displaced or rotated [21][22][23][24] and even excited to interact with one another [25][26][27][28][29]. Moreover, it has already been shown that semiconductor lasers with external injection benefit from an enhanced modulation bandwidth beyond the so-called injection locking point with a much higher resonance frequency (RF) compared to few GHz in typical freerunning devices [30].…”
Section: Introductionmentioning
confidence: 99%